75-3x=10x-23

Simple and best practice solution for 75-3x=10x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 75-3x=10x-23 equation:


Simplifying
75 + -3x = 10x + -23

Reorder the terms:
75 + -3x = -23 + 10x

Solving
75 + -3x = -23 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
75 + -3x + -10x = -23 + 10x + -10x

Combine like terms: -3x + -10x = -13x
75 + -13x = -23 + 10x + -10x

Combine like terms: 10x + -10x = 0
75 + -13x = -23 + 0
75 + -13x = -23

Add '-75' to each side of the equation.
75 + -75 + -13x = -23 + -75

Combine like terms: 75 + -75 = 0
0 + -13x = -23 + -75
-13x = -23 + -75

Combine like terms: -23 + -75 = -98
-13x = -98

Divide each side by '-13'.
x = 7.538461538

Simplifying
x = 7.538461538

See similar equations:

| 4-(2x)=12 | | 20x=15(x+5) | | x+12=28x+3 | | (23x+11)=(14x+21) | | 2x+24=10x-24 | | 3x-4x=1+7x | | 10x+25y=1000 | | 7n-13=5n+5n | | (5x-12)+(-15x+5)= | | x^2-4x+9x-14=0 | | 3(10x-2)=-4(-7+11) | | 5x+12=4-3t | | -3+4x-4x=-26+2x | | x+2(-2)=8 | | 12+2x=4-x | | 3(t-2)=9(t-2) | | 5(x-5)=(14-4) | | 20x+5x-10=90 | | 4-w=3w | | 2r+1=5-11 | | .96y-0.79=0.21y+0.46 | | 6x^2-x+1=3 | | 3x-2x=14+3x | | 6.8y-2.4y=88 | | 2x=5x-2 | | 0.5x+6=x^2+12x | | 0.5x+6=x | | 3p^2-10=-7 | | 4x^2-7x+7=5x+2 | | 2y+9=3 | | 4x^2+3x-729=0 | | x^2+4x-7=-3x+1 |

Equations solver categories